A qualitative meta-synthesis of women's experiences of labor dystocia. Issue 4 (July 2020) - Kissler, Katherine; Jones, Jacqueline; McFarland, A. Kristienne; Luchsinger, Jacalyn
Abstract: Problem: Researchers have prioritized understanding and differentiating the pathophysiologic mechanisms to improve precision in diagnosis and individualization of care, however the experiences of women with labor dystocia have been underexamined. Background: Management of labor dystocia has been identified as an opportunity for reducing the rate of unnecessary cesarean births and the associated risks to women and their infants. This meta-synthesis explores women's experiences of labor dystocia to enrich the discussion of care practices and contextualize discussions of shared decision making in what is most meaningful to women. Questions: How does prolonged labor influence women's experience of birth and motherhood? What are women's experiences with decision-making about labor augmentation during prolonged labor? Methods: Sandelowski and Barroso's meta-synthesis approach was used to analyze primary qualitative studies of women's experiences of labor dystocia. Through inductive thematic synthesis and reciprocal translation, themes identified in qualitative research, quotations, and coded meaning units were aggregated and interpreted into derived categories and themes. Findings: Fourteen qualitative studies were analyzed. Women experienced labor dystocia as a transition from healthy labor to abnormal labor requiring medical support consistent with Transition Theory by Meleis. Six new categories and thirty themes were identified. Each category and theme reflects a distinct component of the experience of labor dystocia. Discussion/conclusion: There is wide variation in the way women experience labor dystocia. Facilitation of the transition from healthy labor to labor dystocia can be supported by a fluid, adaptable method of caring for women in the face of uncertainty and loss of choice.